Fitness Cost of Escape Mutations in p24 Gag in Association with Control of Human Immunodeficiency Virus Type 1 - Martinez-Picado, Javier (American Society for Microbiology, 2006)
Mutational escape by human immunodeficiency virus (HIV) from cytotoxic T-lymphocyte (CTL) recognition is a major challenge for vaccine design. However, recent studies suggest that CTL escape may carry a sufficient cost to viral replicative capacity to facilitate subsequent immune control of a now attenuated virus. In order to examine how limitations can be imposed on viral escape, the epitope TSTLQEQIGW (TW10 [Gag residues 240 to 249]), presented by two HLA alleles associated with effective control of HIV, HLA-B*57 and -B*5801, was investigated. The in vitro experiments described here demonstrate that the dominant TW10 escape mutation, T242N, reduces viral replicative capacity. Structural analysis reveals that T242 plays a critical role in defining the start point and in stabilizing helix 6 within p24 Gag, ensuring that escape occurs at a significant cost. A very similar role is played by Thr-180, which is also an escape residue, but within a second p24 Gag epitope associated with immune control. Analysis of HIV type 1 gag in 206 B*57/5801-positive subjects reveals three principle alternative TW10-associated variants, and each is strongly linked to concomitant additional variants within p24 Gag, suggesting that functional constraints operate against their occurrence alone. The extreme conservation of p24 Gag and the predictable nature of escape variation resulting from these tight functional constraints indicate that p24 Gag may be a critical immunogen in vaccine design and suggest novel vaccination strategies to limit viral escape options from such epitopes.